PENGEMBANGAN VIRTUAL LEARNING SYSTEM (VLS) BERBASIS MOODLE SEBAGAI PLATFORM PEMBELAJARAN ONLINE PADA COVID-19 - Sirwan sirwan; Radhiani Ahyani; Sartika Sartika (Akademika : Jurnal Teknologi Pendidikan, 2021)
The objectives of this research are to; 1) Produce a Virtual Learning System (VLS) Based on Moodle as a Covid-19 Online Learning Platform; 2) Testing the Feasibility of the Virtual Learning System (VLS) from the Appearance and Practicality Aspects. This type of research is Research and Development (R&D) with the Borg and Gall development model. The Borg and Gall model was modified inti six (6) steps, needs analysis, planning, development, Implementation, revision. The subject of the trial involved two media experts, one material experts and 30 student from SMKN 1 Sorong, West Papua were selected randomly. The instrumen used collect data is a product validation questionnaire. The data obtained in the form of qualitative data which are quantified, the tabulated and analyzed descriptively. The results showed that; 1) Research This development has produced a Moodle-based Virtual Learning System (VLS). Moodle-based Virtual Leaning System (VLS) application passed the quality and practicality test by media experts; 2). The results of the trial of the media expert's product on the display aspect obtained a value of 89.5% very feasible criteria, while the practicality aspect was 90.0% practical criteria. Meanwhile, from the aspect of Usabily Virtual Learning system (VLS) based on moodle, 90% of students complete the lesson independently, then 98% of students understand the lesson.